Makanan Khas Bali Di Desa Wisata Bakas Berpotensi Besar Dikembangkan Menjadi Wisata Gastronomi - Sutiarso, Moh Agus; I Nyoman Arto Suprapto; Ni Ketut Alit Sujarmini (Samarinda State Polytechnic, 2024)
Bakas Village is one of the tourist villages in Klungkung Regency, Bali, which has begun to offer gastronomic tourism attractions based on traditions that are still maintained by the local community, namely the tradition of cooking traditional Balinese cuisine. This study was conducted to produce a study that explains how Balinese cuisine can become gastronomic tourism in Bakas Tourism Village. This study was conducted using a primary survey method, namely field observation and interviews with key informants from Bakas Tourism Village. Data collection was supported by a checklist instrument consisting of 7 variables with 28 indicators based on qualitative descriptions from the Guidelines for the Development of Gastronomy Tourism book published by the United Nation World Tourism Organization (UNWTO). It was filled in using the Likert scale method with a score range of 1-5. Furthermore, the results of this checklist were described using quantitative and qualitative descriptive analysis methods. Based on observations and data processing, it was found that Bakas Tourism Village has great potential in developing gastronomic tourism. It's just that there are still several sectors that need to be fixed or developed again by Bakas Tourism Village in order to improve gastronomy in this village.